Operational Dispatch Optimization of an Agrivoltaic System - Soheil Mohseni; Alan Brent (AgriVoltaics Conference Proceedings)
Agrivoltaic systems, which integrate solar photovoltaic (PV) arrays with agricultural land, present a promising solution to enhance both energy and food security by facilitating the simultaneous production of energy and food. However, there is a lack of comprehensive research on the operational strategies required for the efficient and profitable operation of grid-connected agrivoltaic systems. To address this gap, this paper introduces a new method for optimizing the dispatch strategy of agrivoltaic systems. This includes strategies for temporal energy arbitrage with the grid and maximizing self-consumption of excess solar PV generation. The effectiveness of the proposed method is demonstrated through numerical simulations using real-world data from an agrivoltaic system in Aotearoa New Zealand, equipped with stationary battery storage. A conceptual model of a battery-supported agrivoltaic system is used as a test case, focusing on optimizing hourly dispatch to enhance energy efficiency, demand management, and economic viability. The study employs linear programming to optimize the storage system's performance, utilizing 24-hour forecasts for electricity prices, local energy production, and demand. The goal is to charge the storage system when electricity prices are low and discharge it as needed to minimize costs. The results from the application of the method to the case study in Aotearoa New Zealand demonstrate its effectiveness, contributing to the broader goals of energy and food security by enhancing the profitability and reliability of grid-connected agrivoltaic systems.